The Spread of the Invasive Locust Digitate Leafminer Parectopa robiniella Clemens, 1863 (Lepidoptera: Gracillariidae) in Europe, with Special Reference to Ukraine - Volodymyr Tytar; Oksana Nekrasova; Oleksii Marushchak; Mihails Pupins; Arturs Skute; Andris Čeirāns; Iryna Kozynenko (Diversity, 2022)
The spread and outbreaks of phytophagous pests are often associated with global warming. In addition to economic interest, these species may be of interest in terms of biological indication of climate changes. In this context, we considered the locust digitate leafminer Parectopa robiniella Clemens, 1863 (Lepidoptera: Gracillariidae). This phytophage was first discovered in Europe in 1970 near Milano in Italy. Since then, it has been spreading across the continent. In Ukraine, it was recorded for the first time in 2003. In 2020–2021, we found areas of massive leaf damage caused by the black locust (Robinia pseudoacacia) in locations on Trukhaniv Island in Kyiv and some places in the Kyiv administrative region. Using 1041 georeferenced records of P. robiniella across Europe and a Bayesian additive regression trees algorithm (BART), we modeled the distribution of the moth. Predictors of current climate (WorldClim v.2, CliMond v.1.2 and ENVIREM) and a black locust habitat suitability raster were employed. Sets of SDMs built for P. robiniella with and without the habitat suitability raster for the host tree performed equally well. Amongst the factors that determine the niche of the locust digitate leafminer, most important are temperature-related conditions assumed to facilitate the spread and naturalization of the pest. In Ukraine, the appearance of the moth has coincided with increasing mean annual temperatures. Particularly favorable for the species are areas in the west and south-west of the country, and Transcarpathia. In the near future, the moth could reach locations in Nordic countries, Estonia, the British Isles, Black Sea coastal areas in Turkey, further into Russia, etc.